2021
DOI: 10.1111/ene.14790
|View full text |Cite
|
Sign up to set email alerts
|

Untreated patients with multiple sclerosis: A study of French expert centers

Abstract: Background and purpose Disease‐modifying therapies (DMTs) have an impact on relapses and disease progression. Nonetheless, many patients with multiple sclerosis (MS) remain untreated. The objectives of the present study were to determine the proportion of untreated patients with MS followed in expert centers in France and to determine the predictive factors of nontreatment. Methods We conducted a retrospective cohort study. Data were extracted from the 38 centers participating in the European Database for Mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…If, on one hand, this is quite expected on the basis of existing literature, 30 - 32 on the other hand, our finding conflicts with other authors who observed better outcomes in those patients who withdrew their DMTs after a prolonged period without relapses. 33 - 35 However, our data discourage permanent discontinuation or even temporary interruption of the initial DMT even in patients who early achieved the NEDA-3 status and remained stable over time.…”
Section: Discussionmentioning
confidence: 65%
“…If, on one hand, this is quite expected on the basis of existing literature, 30 - 32 on the other hand, our finding conflicts with other authors who observed better outcomes in those patients who withdrew their DMTs after a prolonged period without relapses. 33 - 35 However, our data discourage permanent discontinuation or even temporary interruption of the initial DMT even in patients who early achieved the NEDA-3 status and remained stable over time.…”
Section: Discussionmentioning
confidence: 65%
“…For the present article, we used 0.73 as this value was obtained from a large sample of French RRMS patients followed in tertiary care centres (86% treated; 14% untreated). 5 Among these patients, ARR variability is rather high and overdispersion is supposed to be smaller among very selected MS patients for a phase 3 study. Thus, using an overdispersion value set at 0.73 is probably conservative and usable for most phase 3 studies in RRMS.…”
Section: Discussionmentioning
confidence: 99%
“…For both, we performed one SSE based on the data provided in the statistical analysis plan (expected ARR) and another based on the observed ARR as a sensitivity analysis. For the NB method, overdispersion was set to 0.73, according to the value obtained on a sample of 11,693 French RRMS patients, 5 but was also tested for other overdispersion values between 0.5 and 1.…”
Section: Statistical Methods Usedmentioning
confidence: 99%
“…Also, since 2016, new drugs have been reimbursed and were not considered in this study. However, there are still cases of benign MS that do not require any treatment 12 . Therefore, our conclusions are unlikely to change.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, benign MS cases do not necessarily require the initiation of disease-modifying therapy or hospitalization. Indeed, the number of cases without treatment is estimated at 31% 12 . Furthermore, the accuracy of coding diagnoses in the hospital discharge records for MS is uncertain 13 , 14 .…”
Section: Introductionmentioning
confidence: 99%